2009
DOI: 10.1016/j.pain.2009.04.011
|View full text |Cite
|
Sign up to set email alerts
|

The c-kit signaling pathway is involved in the development of persistent pain

Abstract: Protein kinase signal transduction pathways play critical roles in regulating nociception. Here we show that c-kit, a tyrosine kinase receptor, is expressed in lamina I and II layer of the dorsal horn. Moreover, the superficial c-kit+ fibers originate from the DRG, and c-kit in lamina II inner layer comes from the intrinsic expression of the spinal cord. KitW-v mice, which contain a hypomorphic mutation, exhibited normal acute pain in most pain behavior tests. In formalin test, the first phase was not affected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 34 publications
(47 reference statements)
0
23
0
Order By: Relevance
“…Appropriate execution of this process depends on the structural integrity and electrophysiological properties of the intestinal neurons involved, which are in turn controlled by the SCF/c-Kit axis: SCF is constitutively expressed in various regions of the NS including the CNS, ENS and ANS, but specific expression levels are influenced by external stimuli (54). SCF directly affects neurotransmission by binding its receptor c-Kit and this influences the efficacy of the NS response to external stimuli (12). Indeed, experimental studies in a depression mouse model revealed a correlation between decreased c-Kit expression in the hippocampus and impaired neuronal differentiation and migration (55).…”
Section: Relationship Between the Scf/c-kit Axis And Neuroendocrine-imentioning
confidence: 99%
See 1 more Smart Citation
“…Appropriate execution of this process depends on the structural integrity and electrophysiological properties of the intestinal neurons involved, which are in turn controlled by the SCF/c-Kit axis: SCF is constitutively expressed in various regions of the NS including the CNS, ENS and ANS, but specific expression levels are influenced by external stimuli (54). SCF directly affects neurotransmission by binding its receptor c-Kit and this influences the efficacy of the NS response to external stimuli (12). Indeed, experimental studies in a depression mouse model revealed a correlation between decreased c-Kit expression in the hippocampus and impaired neuronal differentiation and migration (55).…”
Section: Relationship Between the Scf/c-kit Axis And Neuroendocrine-imentioning
confidence: 99%
“…The system composed of SCF and its cognate receptor, c-Kit, is a principal regulator of survival and functionality for a multitude of neural crest-derived cell types, in particular for those involved in visceral perception, smooth muscle contraction and inflammation (1214). Disorders of the neuro-endocrine-immunological network resulting from alterations in the SCF/c-Kit system provide an explanation for the high visceral sensitivity, abnormal bowel contraction strength and low-grade inflammation experienced in IBS, suggesting that this system may be an important target for intervention (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…Thus c-Kit W-v mice exhibited reduced pain behavior in the second phase of the formalin test but showed anomalous persistent, increased mechanical hypersensitivity on the contralateral side after exposure to sciatic nerve chronic constriction injury, a phenomenon not seen in control animals [54]. This murine model cannot be strictly compared to that used by us in our earlier study; those mice carried complete loss-of-function c-Kit alleles, but lethality was reversed by an erythropoietin transgene that rescued c-Kit function in blood cells [31].…”
Section: Discussionmentioning
confidence: 83%
“…A recent study with c-Kit W-v mice that carry a hypomorphic c-Kit allele, in which the kinase activity of c-Kit was reduced by 80%, indicated that c-Kit might play a role in inflammatory and neuropathic pain [54]. Thus c-Kit W-v mice exhibited reduced pain behavior in the second phase of the formalin test but showed anomalous persistent, increased mechanical hypersensitivity on the contralateral side after exposure to sciatic nerve chronic constriction injury, a phenomenon not seen in control animals [54].…”
Section: Discussionmentioning
confidence: 99%
“…7 SCF/c-kit is a principal regulator for survival and function of a multitude of neural crest-derived cell types, particularly for those involved in smooth muscle contraction and inflammation. [8][9][10] Our previous study found that peripheral serum SCF/c-kit levels increase in pre-hypertensive and hypertensive patients. 11 However, the relationship between SCF/c-kit and the type of hypertension (dipper or non-dipper)…”
mentioning
confidence: 95%